10.1002/9781118797914 (CrossRef Listing of Deleted DOIs, 2000)
Objective Real-world evidence on inebilizumab among neuromyelitis optica spectrum disorder (NMOSD) patients is lacking. This study assessed inebilizumab among Chinese patients with aquaporin 4 autoantibody (AQP4-IgG)-seropositive NMOSD in a real-world setting. Methods This multicenter, prospective, observational study enrolled patients with AQP4-IgG-seropositive NMOSD who received at least one dose of inebilizumab. The primary outcome was the time to first adjudicated NMOSD attack. Results A total of 143 patients with AQP4-IgG-seropositive NMOSD were included. Over a median follow-up of 12.4 months (range: 0.4-25.4), five patients (3.50%) experienced attacks, with a 1-year cumulative incidence of 4.54% (95% confidence interval, 1.66-9.70). Annualized attack rate decreased from 1.02 to 0.03 after inebilizumab treatment, and the Expanded Disability Status Scale scores were significantly improved, with a median change of -0.50 (range, -5.0 to 1.5; p < 0.0001; worsening rate, 0.70%) at 1 year. The most common treatment-emergent adverse events were urinary tract infection (6.29%), and one case of pneumonia (0.70%) was reported as serious adverse event. B-cell depletion was effectively achieved, with only 1 patient reporting hypogammaglobulinemia. Conclusion Inebilizumab demonstrated real-world effectiveness and a manageable safety profile in a diverse population of patients with AQP4-IgG-seropositive NMOSD, supporting the findings of the pivotal N-MOmentum trial.